The reality of agricultural activity (in the vegetable plot) in Daraa governorate and its development between 1990 and 2010 (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The natural factors affecting agricultural production negatively or positively, but are often the determinant factor of the quality of the crop and to the degree of success, and despite the successful man to overcome some of the difficulties and constraints imposed by the natural factors of climate, water, soil and terrain and other factors of nature, Its impact on agriculture remains high and above human capacity to the extent that it guides human activities in this field.Cereals are one of the most important agricultural crops in Daraa governorate, the most widespread and the most widely used. The main food is the basic food for the people of the province.The production and production of fruit trees occupies a prominent position within the economic activities in Daraa governorate, where the products of these trees contribute to securing a section of the food needs of the population and contribute to securing job opportunities for a large number of the population of this governorate and play an important role in providing raw raw materials for some industries , And the role of trees in improving the environment. The availability of environmental and human conditions in the governorate of Daraa has led to the spread of various types of fruit trees, which are spread throughout the governorate and concentrated in the first and second stabilization zone,